Flexible ceramic mineral insulated high-flame-retardant fireproof cable and processing technology thereof
By using flexible ceramic mineral insulated high-fire-retardant fire-resistant cables, combined with specific twisting and wrapping processes, the problem of degradation of insulation performance of existing cables in high temperature and high humidity environments is solved, and efficient insulation and flame-retardant performance is achieved, ensuring the reliability and safety of the cables.
Patent Information
- Application Number
- CN202510027606.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The insulation performance of existing flame-retardant fire-resistant cables may decline in high temperature and high humidity environments, and the connection technology is not reliable enough, which can easily lead to problems such as increasing contact resistance and heating.
Flexible ceramicized mineral insulated high flame retardant fire-retardant cables, including copper conductors, ceramicized mica tape insulation layer, ceramicized silicone tape and low-smoke halogen-free flame retardant polyolefin sheath, improve the insulation and flame retardant performance of the cable through specific twisting and wrapping processes.
It achieves good insulation performance under high temperature and high humidity environments, improves the fire resistance and mechanical properties of the cable, and ensures the reliability and safety of the cable.
Smart Images

Figure CN119864202A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cable device, in particular to a flexible ceramic mineral insulated highly flame-retardant and fireproof cable and a processing technology thereof, belonging to the technical field of flame-retardant and fireproof cables. Background Art
[0002] Flame-retardant fireproof cable refers to the cable that can maintain safe operation for a certain period of time under flame burning. It is suitable for fire protection lines, mining industry, nuclear industry and other places. It is often used for alarm lines exceeding the predetermined temperature. Due to the defects of rigid mineral insulated cables in reliability, production and laying, flexible mineral insulated fireproof cables have become the mainstream cable products in the field of fire protection.
[0003] For example, the patent document CN114171247A discloses a ceramicized polyolefin insulated highly flame-retardant fireproof cable and its preparation process, which provides the cable with excellent insulation by providing an inner lining layer, a ceramicized oxygen-isolating layer, a glass fiber tape and a low-smoke halogen-free outer sheath. However, in actual use, especially in the fields of wires and cables, electrical equipment, etc., the demand for high temperature resistance of cables is stronger. The insulation performance of the glass fiber tape may decrease in harsh environments such as high temperature and high humidity. In addition, the connection technology of some traditional cables in the prior art is not reliable enough, which may easily lead to problems such as increased contact resistance and heat generation. In view of this, the present application proposes a flexible ceramicized mineral insulated highly flame-retardant fireproof cable and its processing technology and its processing technology. Summary of the invention
[0004] The purpose of the present invention is to provide a flexible ceramic mineral insulated highly flame retardant and fireproof cable and its processing technology in order to solve the above problems.
[0005] The present invention achieves the above-mentioned purpose through the following technical scheme: a flexible ceramic mineral insulated highly flame-retardant fireproof cable, comprising a conductor, an insulating layer, a flame-retardant filling rope, a ceramic silicone tape and a sheath, the copper conductors are arranged in five groups, the five conductors are connected to each other, the outside of the conductors are wrapped with an insulating layer, the conductors and the insulating layers are arranged in five equal parts with the intersection of the axis connection as the center of the circle, a flame-retardant filling rope is provided on the outside of the insulating layer, a ceramic silicone tape is provided on the outside of the flame-retardant filling rope, and a sheath is provided on the side of the ceramic silicone tape away from the flame-retardant filling rope.
[0006] Preferably, the conductor is made of copper, and the insulating layer is made of high-purity phlogopite. During the production process, fine grinding and screening are performed to ensure that the thickness uniformity of the mica sheet is within ±5μm, thereby improving the density of the insulating layer. The flame retardant filling rope is a ceramic silicone rubber filling rope, and the sheath is made of low-smoke halogen-free flame retardant polyolefin.
[0007] Preferably, the raw materials of the ceramic silicone belt are: silicone rubber with an ethylene content of 0.23% and a molecular weight of 650,000-950,000; ceramic powder with an average particle size of 4 μm and an alumina content of more than 99.9%; 12% of flame retardant and borate glass powder with a particle size of 0.3-2 μm; 1.8% of KH550 as a coupling agent; and 0.8% of fatty acid ester as a lubricant.
[0008] The above-mentioned processing technology of a flexible ceramic mineral insulated highly flame retardant and fireproof cable includes the following processing steps:
[0009] S1. Raw material preparation: select high-purity oxygen-free copper rod with a copper content of 99.99% as the material of the conductor, select ceramic mica tape as the material of the insulating layer, select magnesium oxide powder with a purity of 99% as an inorganic flame retardant, prepare silicone rubber with an ethylene content of 0.23% and a molecular weight of 650,000-950,000; ceramic powder with an average particle size of 4μm and an aluminum oxide content of more than 99.9%; 12% of flame retardant, borate glass powder with a particle size of 0.3-2μm; KH550 as a coupling agent at a dosage of 1.8%; fatty acid esters as a lubricant at a dosage of 0.8% for making the ceramic silicone tape, prepare low-smoke halogen-free flame-retardant polyolefin with a melt flow rate of 2g / 10min as the material of the sheath, and add 2%-3% nano-montmorillonite and 5%-8% magnesium hydroxide to the low-smoke halogen-free flame-retardant polyolefin formula;
[0010] S2. Conductor twisting: preheat the single-filament copper conductor at 95-105℃ for 10-15 minutes, and twist it in layers. The inner and outer twisting directions are opposite. The right pitch of the inner layer is 10-13 times the conductor diameter, and the left pitch of the outer layer is 15-18 times. The tension is within ±3%;
[0011] Preheat the monofilament copper conductor at 95-105℃ for 10-15 minutes, and twist it in layers, with the inner and outer twisting directions opposite, the inner layer right pitch is 10-13 times the conductor diameter, and the outer layer left pitch is 15-18 times, with the tension within ±3%;
[0012] S3, insulation wrapping, firstly, the copper conductor is ultrasonically cleaned and passivated, and the ceramic mica tape is wrapped in the twisting direction of the copper conductor, with 3 layers and an overlap rate of 15%;
[0013] S4, cabling, twisting five insulated wire cores into a cable core in a star-twisted arrangement. During the cabling process, magnesium oxide powder is added as an inorganic flame retardant to fill the gaps between the wire cores. A precise metering spiral feeding device is used to control the filling amount of magnesium oxide powder, and the filling factor is 0.8-0.85;
[0014] S5, wrapping protection, use cleaning tools to remove dust, oil and other impurities on the surface of the cable core to ensure that the surface of the cable core is clean, and then place the ceramic silicone tape on the special pay-off stand of the wrapping equipment, adjust the pay-off tension through the tension closed-loop control system, and control the tension fluctuation within ±2%. Start the wrapping machine to make the cable core start to rotate at a constant speed or pull forward at a constant speed. At the same time, the ceramic silicone tape is wrapped around the outside of the cable core according to the set 3-layer wrapping and 15% overlap rate;
[0015] S6, sheath extrusion, low smoke halogen-free flame retardant polyolefin, nano montmorillonite, magnesium hydroxide and other materials are fully mixed in a high-speed mixer, stirred at 1300-1800r / min for 25-32 minutes, screw speed 38-40r / min, extrusion temperature 155-185℃, sheath thickness 1.4-1.6mm (±0.06mm deviation), first 16-20℃ water cooling for 3-4 minutes, then 24-28℃ air cooling for 7-9 minutes;
[0016] S7. Performance testing: Conduct line integrity tests in accordance with GB / T19216.21-2003 and GB / T19216.2-2021 standards.
[0017] Preferably, during the twisting process, the DC resistance of the conductor does not exceed 0.017241Ω·mm at 20°C. 2 / m.
[0018] Preferably, before being added to the low-smoke halogen-free flame-retardant polyolefin, the nano-montmorillonite is first mixed with an appropriate amount of polyethylene wax in a high-speed mixer at a stirring speed of 1000-1500 r / min for 20-30 minutes.
[0019] Preferably, the ceramic silicone belt raw material is first stirred at a low speed of 300-500 r / min for 6-9 minutes at 40-60° C., and then kneaded at a high speed of 1000-1500 r / min for 25-35 minutes.
[0020] The present invention has the following beneficial effects:
[0021] 1. The flexible ceramic mineral insulated high flame retardant fireproof cable made of copper conductor, three layers of ceramic mica tape, overlap rate of 15%, ceramic silicone rubber filling rope, ceramic silicone tape, and low-smoke halogen-free flame retardant polyolefin sheath has good insulation and high flame retardant fireproof performance, and meets the inspection requirements of GB / T19216.21-2003 "Line integrity test of cables or optical cables under flame conditions Part 21: Test procedures and requirements-Rated voltage 0.6 / 1.0kV and below cables"; GB / T19216.2-2021 "Line integrity test of cables or optical cables under flame conditions Part 2: Test method for cables with rated voltage 0.6 / 1kV and below and outer diameter not exceeding 20mm with fire supply and impact vibration with flame temperature not less than 830C";
[0022] 2. The use of oxygen-free copper as the material of flexible ceramic mineral insulated highly flame-retardant fireproof cable conductor has excellent advantages in conductivity, flexibility and corrosion resistance, and improves the fire retardancy of the cable;
[0023] 3. The ceramic silicone belt made of the following weight percentages: silicone rubber with 0.23% ethylene content and molecular weight of 650,000-950,000; ceramic powder with an average particle size of 4μm and an alumina content of more than 99.9%; 12% flame retardant, borate glass powder with a particle size of 0.3-2μm; KH550 as a coupling agent at a dosage of 1.8%; and fatty acid esters as a lubricant at a dosage of 0.8%, has higher flame retardancy, better high temperature resistance, and good mechanical and processing properties;
[0024] 4. The ceramic mica tape is wrapped with three layers, with an overlap rate of 15%, forming a thicker and more stable protective layer, improving the fire resistance limit, strengthening the multi-layer insulation, having stable electrical isolation, being able to resist external force impact, improving tensile and tear resistance, and being able to adapt to different cable structures and work synergistically with other materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A structural cross-sectional diagram of a flexible ceramic mineral insulated highly flame-retardant fireproof cable proposed by the present invention;
[0026] Figure 2 A summary table of test results of a flexible ceramic mineral insulated highly flame retardant and fireproof cable proposed by the present invention;
[0027] Figure 3 This is a comparison chart before and after the line integrity test of a flexible ceramic mineral insulated high flame retardant fireproof cable proposed by the present invention according to GB / T19216.21-2003;
[0028] Figure 4This is a comparison chart before and after the complete line test of a flexible ceramic mineral insulated highly flame-retardant and fire-proof cable proposed in the present invention according to GB / T19216.2-2021.
[0029] In the figure: 1. Conductor; 2. Insulation layer; 3. Flame-retardant filling rope; 4. Ceramic silicone tape; 5. Sheath. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0031] A flexible ceramic mineral insulated highly flame-retardant fireproof cable comprises a conductor 1, an insulating layer 2, a flame-retardant filling rope 3, a ceramic silicone tape 4 and a sheath 5. The copper conductors 1 are arranged in five groups. The five conductors 1 are connected to each other. The outer sides of the conductors 1 are wrapped with insulating layers 2. The conductors 1 and the insulating layers 2 are arranged in five equal parts with the intersection of the axis connection as the center of the circle. The outer side of the insulating layer 2 is provided with a flame-retardant filling rope 3, the outer side of the flame-retardant filling rope 3 is provided with a ceramic silicone tape 4, and the side of the ceramic silicone tape 4 away from the flame-retardant filling rope 3 is provided with a sheath 5.
[0032] The conductor 1 is made of copper, and the insulating layer 2 is made of high-purity phlogopite. During the production process, fine grinding and screening are performed to ensure that the thickness uniformity of the mica sheet is within ±5μm, thereby improving the density of the insulating layer. The flame-retardant filling rope 3 is a ceramic silicone rubber filling rope, and the sheath 5 is made of low-smoke halogen-free flame-retardant polyolefin.
[0033] Specifically, a processing technology of a flexible ceramic mineral insulated highly flame retardant and fireproof cable includes the following processing steps:
[0034] Step 1: Raw material preparation:
[0035] A high-purity oxygen-free copper rod with a copper content of 99.99% is selected as the material of the conductor, a ceramic mica tape is selected as the material of the insulating layer, and a magnesium oxide powder with a purity of 99% is selected as an inorganic flame retardant. Silicone rubber with an ethylene content of 0.23% and a molecular weight of 650,000-950,000 is prepared; ceramic powder with an average particle size of 4μm and an aluminum oxide content of more than 99.9%; 12% of a flame retardant and borate glass powder with a particle size of 0.3-2μm; KH550 is used as a coupling agent at a dosage of 1.8%; a fatty acid ester lubricant at a dosage of 0.8% is used to make the ceramic silicone tape, a low-smoke halogen-free flame-retardant polyolefin with a melt flow rate of 2g / 10min is prepared as the material of the sheath, and 2%-3% of nano-montmorillonite and 5%-8% of magnesium hydroxide are added to the low-smoke halogen-free flame-retardant polyolefin formula;
[0036] Step 2: Conductor twisting:
[0037] Preheat the monofilament copper conductor at 95-105℃ for 10-15 minutes, and twist it in layers. The inner and outer twisting directions are opposite. The right pitch of the inner layer is 10-13 times the conductor diameter, and the left pitch of the outer layer is 15-18 times. The tension is within ±3%. During the twisting process, the DC resistance of conductor 1 does not exceed 0.017241Ω·mm at 20℃ 2 / m.
[0038] Step 3: Insulation wrapping:
[0039] First, the copper conductor is ultrasonically cleaned and passivated, and the ceramic mica tape is wrapped in the twisting direction of the copper conductor, with 3 layers and an overlap rate of 15%;
[0040] Step 4: Cable formation:
[0041] Five insulated wire cores are twisted into a cable core in a star-twisted arrangement. During the cabling process, magnesium oxide powder is added as an inorganic flame retardant to fill the gaps between the wire cores. A precision metering spiral feeding device is used to control the filling amount of magnesium oxide powder, and the filling factor is 0.8-0.85;
[0042] Step 5: Wrapping protection:
[0043] Use cleaning tools to remove dust, oil and other impurities on the surface of the cable core to ensure that the surface of the cable core is clean, then place the ceramic silicone tape 5 on the special pay-off stand of the wrapping equipment, adjust the pay-off tension through the tension closed-loop control system, and control the tension fluctuation within ±2%. Start the wrapping machine to make the cable core start to rotate at a constant speed or pull forward at a constant speed. At the same time, the ceramic silicone tape 4 is wrapped around the outside of the cable core according to the set 3-layer wrapping and 15% overlap rate;
[0044] Step 6: Sheath extrusion:
[0045] The low-smoke halogen-free flame-retardant polyolefin, nano-montmorillonite, magnesium hydroxide and other materials are fully mixed in a high-speed mixer, stirred at 1300-1800r / min for 25-32 minutes, the screw speed is 38-40r / min, the extrusion temperature is 155-185℃, the jacket thickness is 1.4-1.6mm (±0.06mm deviation), first cooled in water at 16-20℃ for 3-4 minutes, and then cooled in air at 24-28℃ for 7-9 minutes;
[0046] Step 7: Performance testing:
[0047] The line integrity test is carried out in accordance with GB / T19216.21-2003 "Line integrity test of cables or optical cables under flame conditions Part 21: Test procedures and requirements - Cables with rated voltage of 0.6 / 1.0kV and below"; GB / T19216.2-2021 "Line integrity test of cables or optical cables under flame conditions Part 2: Test method for cables with rated voltage of 0.6 / 1kV and below and outer diameter not exceeding 20mm with fire and impact vibration with a flame temperature of not less than 830C" standards.
[0048] Before being added into the low-smoke halogen-free flame-retardant polyolefin, the nano-montmorillonite is first mixed with an appropriate amount of polyethylene wax in a high-speed mixer at a stirring speed of 1000-1500r / min for 20-30 minutes.
[0049] Embodiment 1:
[0050] Preparation of ceramic silicone belt (I)
[0051] Ceramic silicone tape 4 prepares methyl vinyl silicone rubber: 100 parts, low-temperature glass powder: 20 parts, high-temperature glass powder: 50 parts, methoxy silicone oil: 3 parts, mica powder: 30 parts, silicon micropowder: 45 parts, silane coupling agent: 0.1 parts, white carbon black 20 parts, and the amount of vulcanizing agent is 1.1% of the total weight of the components (the vulcanizing agent is 2,4-dichlorobenzoyl peroxide).
[0052] Dry silicone rubber with a vinyl content of 0.2% and a molecular weight of 500,000-800,000 at 60-80°C in a vacuum (0.08-0.1 MPa) for 4-6 hours.
[0053] Select ceramic powder with an average particle size of 8 μm and an alumina content of more than 99.5%, and modify it with KH560 (2% dosage) at 60-70° C. and 1000-1200 r / min for 2-3 hours.
[0054] Flame retardant: 11.5% nitrogen-phosphorus series (phosphate esters), premixed at 800-1200r / min for 10-15 minutes. Premixing ensures uniform dispersion, improves flame retardancy, and the limiting oxygen index reaches 40%-45%.
[0055] Flux: Borate glass powder with softening temperature of 500-600℃ and particle size of 1-5μm.
[0056] Coupling agent: KH550 is used at 1.5% and diluted with ethanol at a ratio of 1:5-1:10. Then, it is added to the raw material and stirred at 800-1200 r / min for 5-10 minutes.
[0057] Antioxidant: Hindered phenols (such as 1010) at 0.7% dosage, micronized to a particle size of 1-3 μm, inhibit oxidative degradation, and the mechanical properties retention rate after high-temperature aging at 150°C for 1000 hours is 80%-90%.
[0058] Lubricant: 0.7% fatty acid ester, melted at 40-60°C, then added and stirred at 300-500r / min for 3-5 minutes to reduce the friction coefficient and the extrusion pressure by 10%-15%.
[0059] Mixing: 40-60℃, stir at low speed of 300-500r / min for 5-10 minutes, then mix at high speed of 800-1200r / min for 15-30 minutes.
[0060] Molding: The temperature from extruder hopper to die head is 40-50℃, 50-60℃, 60-70℃, 70-80℃, and the speed is 5-10m / min.
[0061] Vulcanization: 150-200℃ vulcanization, adjust the time according to the thickness of the product, 0.5-1.5MPa pressure.
[0062] Embodiment 2:
[0063] Preparation of ceramic silicone belt (Part 2)
[0064] Ceramic silicone tape 4 prepares methyl vinyl silicone rubber: 100 parts, low-temperature glass powder: 50 parts, high-temperature glass powder: 20 parts, methoxy silicone oil: 5 parts, mica powder: 20 parts, silicon micropowder: 40 parts, silane coupling agent: 0.3 parts, white carbon black 40 parts, and the amount of vulcanizing agent is 1.0% of the total weight of the components (the vulcanizing agent is 2,4-dichlorobenzoyl peroxide).
[0065] Silicone rubber: vinyl content 0.22%, molecular weight 600,000-900,000, vacuum dried at 70°C for 5 hours, the vulcanization performance is further improved, and the tensile strength is increased by 15%-20% compared with the first embodiment.
[0066] Ceramic powder: average particle size 6μm, alumina content above 99.8%, KH550 (2.5% dosage) 65-75℃, 1000-1300r / min modified for 3 hours to form a denser ceramic structure, and the high temperature resistance is improved to 1300-1400℃.
[0067] Flame retardant: Nitrogen-phosphorus series, 11.8% dosage, premixed at 1000-1300r / min for 15 minutes, the flame retardant effect is enhanced, and the limiting oxygen index reaches 45%-50%.
[0068] Flux: Borate glass powder with softening temperature of 450-550℃ and particle size of 0.5-3μm, to optimize the fluxing effect.
[0069] Coupling agent: KH550 is used at 1.6%, diluted with ethanol at 1:8, and then added to the raw material at 1000-1300 r / min and stirred for 8 minutes. The elongation at break is increased by 20%-25% compared with Example 5. Antioxidant: Hindered phenols (such as 1076) are used at 0.75%, micronized to a particle size of 0.8-2 μm, and the mechanical property retention rate after high temperature aging at 150°C for 1000 hours is 85%-95%.
[0070] Lubricant: 0.75% fatty acid ester, melted at 50°C, added and stirred at 400 r / min for 4 minutes, the extrusion pressure was reduced by 15%-20%.
[0071] Mixing: 40-60℃, stir at low speed of 300-500r / min for 8-12 minutes, then mix at high speed of 1000-1300r / min for 20-30 minutes.
[0072] Molding: The temperature from extruder hopper to die head is 40-55℃, 55-65℃, 65-75℃, 75-80℃, and the speed is 6-10m / min.
[0073] Vulcanization: 160-190℃ vulcanization, adjust the time according to the thickness of the product, 0.8-1.2MPa pressure.
[0074] Embodiment three:
[0075] Preparation of ceramic silicone belt (III (i.e., the preparation process of ceramic silicone belt proposed in the present application))
[0076] Prepare 100 parts of methyl vinyl silicone rubber, 35 parts of low-temperature glass powder, 35 parts of high-temperature glass powder, 4 parts of methoxy silicone oil, 35 parts of mica powder, 35 parts of silicon micropowder, 0.3 parts of silane coupling agent, and 30 parts of white carbon black. The amount of vulcanizer is 0.8% of the total weight of the components (the vulcanizer is 2,4-dichlorobenzoyl peroxide).
[0077] Silicone rubber: Vinyl content 0.23%, molecular weight 650,000-950,000, vacuum drying at 70-90℃ for 3-5 hours, vulcanization and mechanical properties are further improved.
[0078] Ceramic powder: average particle size 4μm, alumina content above 99.9%, KH792 (3% dosage) 60-80℃, 1000-1500r / min modified for 3-4 hours, greatly improves compatibility with silicone rubber and promotes ceramic reaction.
[0079] Flame retardant: High-efficiency nitrogen-phosphorus system, 12% dosage, premix at 1000-1500r / min for 15-20 minutes to ensure uniform dispersion.
[0080] Flux: Borate glass powder with softening temperature of 400-500℃ and particle size of 0.3-2μm, which accelerates the ceramic reaction process.
[0081] Coupling agent: KH550 is used at a dosage of 1.8%, diluted with 1:6 isopropanol, and then added to the raw materials at 1000-1500r / min and stirred for 10-12 minutes to strongly improve the interfacial bonding strength.
[0082] Antioxidant: Hindered phenols (such as 3114) at 0.8%, micronized to a particle size of 0.5-1.5 μm, effectively inhibiting oxidative degradation.
[0083] Lubricant: 0.8% fatty acid ester, melted at 50-70℃, then added and stirred at 400-600r / min for 4-6 minutes to reduce the processing friction coefficient.
[0084] Mixing: 40-60℃, stir at low speed of 300-500r / min for 6-9 minutes, then mix at high speed of 1000-1500r / min for 25-35 minutes.
[0085] Molding: extruder hopper to die head temperature 40-52℃, 52-62℃, 62-72℃, 72-80℃, speed 7-12m / min.
[0086] Vulcanization: 170-200℃ vulcanization, adjust the time according to the thickness of the product, 1-1.5MPa pressure.
[0087] Embodiment 4:
[0088] According to the above-mentioned embodiments 1, 2 and 3, the ceramic silicone belt ratios in the above-mentioned three embodiments are compared by parameters:
[0089]
[0090]
[0091]
[0092]
[0093]
[0094] According to the comparison of the above embodiments, compared with Embodiment 1, the vinyl content and molecular weight of the silicone rubber in Embodiments 2 and 3 are adjusted, and the drying conditions are also changed, so that the vulcanization performance is gradually improved; the particle size of the ceramic powder is smaller, the purity is higher, and the modification process is more optimized, which improves the compatibility with silicone rubber and high temperature resistance; the amount of flame retardant and the premixing process are improved, which enhances the flame retardant effect; the amount and treatment method of coupling agent, antioxidant and lubricant are optimized, which improves the comprehensive performance of the material, such as mechanical properties, antioxidant properties and processing properties.
[0095] On the basis of Example 2, Example 3 (i.e., the raw material ratio of the ceramic silicone tape in the present application) further optimizes the parameters and processing technology of each raw material, so as to further improve the performance of the ceramic silicone tape, such as high temperature resistance, mechanical properties and flame retardant properties.
[0096] Embodiment five:
[0097] Cable processing technology (I)
[0098] Conductor twisting: Preheat the single-filament copper conductor to 80-100℃ for 10-15 minutes, twist it in layers, the inner layer right-hand twist pitch is 12-18 times the conductor diameter, the outer layer left-hand twist pitch is 18-25 times, and the tension uniformity is within ±5%.
[0099] Insulation wrapping: ultrasonic cleaning 20-30kHz, 5-8 minutes, passivation treatment 0.5%-1% chromate passivation solution for 3-5 minutes, insulation tape tension 8-12N, speed 8-12m / min, wrapping number of layers 3, overlap rate 15%.
[0100] Cabling: Preheat the insulated core to 60-80℃ for 5-8 minutes, the filling factor of magnesium oxide powder is 0.8-0.85, and the cable is made by rotating mold, with a twisting pitch of 80-120mm.
[0101] Wrapping protection: high-pressure airflow 0.8-1.2MPa and electrostatic adsorption 5-8kV to clean the cable core, ceramic silicone tape pay-off tension within ±3%, wrapping speed 10-15m / min, temperature 35-55℃, thickness uniformity within ±0.05mm.
[0102] Sheath extrusion: material mixing and stirring at 1000-1500r / min for 20-30 minutes, screw speed 35-45r / min, extrusion temperature 150-190℃, sheath thickness 1.2-1.8mm, thickness deviation within ±0.1mm, water cooling followed by air cooling.
[0103] Embodiment six:
[0104] Cable processing technology (II (similar to Example 5, with some parameters optimized))
[0105] Conductor twisting: Preheat the single-filament copper conductor at 90-100℃ for 8-12 minutes, and twist it in layers (the right-hand pitch of the inner layer is 10-14 times the conductor diameter, the left-hand pitch of the outer layer is 16-20 times, and the tension is within ±4%).
[0106] Insulation wrapping: After the conductor is ultrasonically cleaned (22-28kHz, 6-7 minutes), it is passivated with 0.6%-0.9% chromate passivation solution for 3-4 minutes. The insulation tape is wrapped with 3 layers at a tension of 9-11N and a speed of 9-11m / min, with an overlap rate of 15%.
[0107] Cabling: Preheat the insulated core at 65-75℃ for 6-7 minutes, the filling factor of magnesium oxide powder is 0.82-0.84, and the cabling is made by rotary mold, with a twisting pitch of 70-90mm.
[0108] Wrapping protection: 1-1.3MPa high-pressure airflow and 6-7.5kV electrostatic adsorption to clean the cable core, ceramic silicone tape pay-off tension within ±2%, 11-13m / min wrapping speed, 40-48℃ temperature control, thickness uniformity within ±0.04mm.
[0109] Sheath extrusion: material is stirred at 1200-1600r / min for 22-28 minutes, screw speed is 36-42r / min, extrusion temperature is 152-188℃, sheath thickness is 1.3-1.7mm (±0.08mm deviation), first cooled in water at 18-22℃ for 3-4 minutes, then air cooled at 22-26℃ for 6-8 minutes.
[0110] Embodiment seven:
[0111] Cable processing technology (three (compared with the above embodiment, further optimizing the parameters, i.e., the cable processing technology proposed in the present invention))
[0112] Conductor twisting: Preheat the single-filament copper conductor at 95-105℃ for 10-15 minutes, and twist it in layers (the right-hand pitch of the inner layer is 10-13 times the conductor diameter, the left-hand pitch of the outer layer is 15-18 times, and the tension is within ±3%).
[0113] Insulation wrapping: After the conductor is ultrasonically cleaned (24-26kHz, 7-8 minutes), it is passivated with 0.7%-0.8% chromate passivation solution for 4-5 minutes. The insulating tape is wrapped with 3 layers at a tension of 10-11N and a speed of 10-11m / min, with an overlap rate of 15%.
[0114] Cabling: Preheat the insulated core at 70-78℃ for 6-7 minutes, the filling factor of magnesium oxide powder is 0.83-0.85, and the cable is made by rotary mold, with a twisting pitch of 75-85mm.
[0115] Wrapping protection: 1.2-1.5MPa high-pressure airflow and 7-8.5kV electrostatic adsorption to clean the cable core, ceramic silicone tape pay-off tension within ±1.5%, 12-14m / min wrapping speed, 42-46℃ temperature control, thickness uniformity within ±0.03mm.
[0116] Sheath extrusion: material 1300-1800r / min stirring for 25-32 minutes, screw speed 38-40r / min, extrusion temperature 155-185℃, sheath thickness 1.4-1.6mm (±0.06mm deviation), first 16-20℃ water cooling for 3-4 minutes, then 24-28℃ air cooling for 7-9 minutes
[0117] Embodiment eight:
[0118] According to the above embodiments 5, 6 and 7, the cable processing techniques in the above three embodiments are compared by parameters:
[0119]
[0120]
[0121]
[0122]
[0123] In summary, in embodiments 6 and 7, when the conductors are twisted, the preheating temperature, twisting parameters and tension control are more precise, so that the conductor performance is better; the ultrasonic cleaning frequency, passivation liquid concentration and winding parameters of the insulation winding are optimized, which improves the quality of the insulation layer; the preheating temperature, filling factor and twisting pitch are adjusted during cabling to improve the stability of the cable core structure; the cleaning method, tension control, winding speed and temperature control of the winding protection are more refined, which enhances the protection effect; the material stirring speed, screw speed, extrusion temperature and cooling method of the sheath extrusion are optimized, which improves the sheath performance.
[0124] In general, as the serial number of the embodiments increases, the ratio and process are continuously optimized, and the performance of the cable is gradually improved, such as insulation performance, flame retardancy, high temperature resistance, mechanical performance, etc. Embodiment 7 performs best in all aspects and can better meet the needs of flexible ceramic mineral insulated high flame retardant fireproof cables.
[0125] Embodiment nine:
[0126] Flexible ceramic mineral insulated high flame retardant fireproof cable made of copper conductor, ceramic mica tape (three layers of wrapping, overlap rate 15%), ceramic silicone rubber filling rope, ceramic silicone tape, low smoke zero halogen flame retardant polyolefin sheath can be tested in GB / T19216.21-2003 test with applied voltage of cable rated voltage 0.6 / 1kV, fire supply temperature: 950℃-1000℃, fire exposure time 180min. After 90min of fire exposure and 15min of cooling, the line remains intact, and the 2A fuse is not broken and the indicator light is not extinguished;
[0127] In the line integrity test (GB / T19216.2-2021) of a flexible ceramic mineral insulated high flame retardant fireproof cable in the present invention, the voltage applied to the sample is the rated voltage of the cable 0.6 / 1kV, the fire temperature is (830-870)°C, the fire time is 30min; the impact starts 5min±10s after the fire, and the impact is once every 5min±10s;
[0128] According to the inspection of GB / T19216.21-2003 "Line integrity test of cables or optical cables under flame conditions Part 21: Test procedures and requirements - Cables with rated voltage of 0.6 / 1.0kV and below" and GB / T19216.2-2021 "Line integrity test of cables or optical cables under flame conditions Part 2: Test method for cables with rated voltage of 0.6 / 1kV and below with an outer diameter not exceeding 20mm, with a flame temperature not less than 830C and impact vibration", the inspection results of the BTGE-0.6 / 1kV5X6 rated voltage 0.6 / 1kV flexible ceramic mineral insulated high flame retardant fireproof test cable meet the requirements of the standard (refer to the attached manual Figure 2-4 shown).
Claims
1. A flexible ceramic mineral insulated highly flame retardant fireproof cable, characterized in that: The invention comprises a conductor (1), an insulating layer (2), a flame retardant filling rope (3), a ceramic silicone tape (4) and a sheath (5), wherein the copper conductor (1) is arranged in five groups, the five conductors (1) are connected to each other, the outer side of each conductor (1) is wound with an insulating layer (2), the conductor (1) and the insulating layer (2) are arranged in five equal parts with the intersection of the axis connection as the center of the circle, the outer side of the insulating layer (2) is provided with a flame retardant filling rope (3), the outer side of the flame retardant filling rope (3) is provided with a ceramic silicone tape (4), and the ceramic silicone tape (4) is provided with a sheath (5) on the side away from the flame retardant filling rope (3).
2. A flexible ceramic mineral insulated highly flame retardant and fireproof cable according to claim 1, characterized in that: The conductor (1) is made of copper, the insulating layer (2) is made of high-purity phlogopite, the thickness uniformity of the mica sheet is within ±5 μm, and the compactness of the insulating layer is improved. The flame-retardant filling rope (3) is a ceramic silicone rubber filling rope, and the sheath (5) is made of low-smoke halogen-free flame-retardant polyolefin.
3. A flexible ceramic mineral insulated highly flame retardant and fireproof cable according to claim 2, characterized in that: The raw materials of the ceramic silicone tape (4) are: silicone rubber with an ethylene content of 0.23% and a molecular weight of 650,000-950,000; ceramic powder with an average particle size of 4 μm and an aluminum oxide content of more than 99.9%; 12% of a flame retardant, borate glass powder with a particle size of 0.3-2 μm; KH550 as a coupling agent in an amount of 1.8%; and fatty acid esters as a lubricant in an amount of 0.8%. Silicone rubber with an ethylene content of 0.23% and a molecular weight of 650,000-950,000; ceramic powder with an average particle size of 4 μm and an aluminum oxide content of more than 99.9%; 12% of a flame retardant, borate glass powder with a particle size of 0.3-2 μm; KH550 as a coupling agent in an amount of 1.8%; and fatty acid esters as a lubricant in an amount of 0.8%.
4. A processing technology for a flexible ceramic mineral insulated highly flame retardant and fireproof cable as described in any one of claims 1 to 3, characterized in that: The processing steps include: S1. Raw material preparation: selecting a high-purity oxygen-free copper rod with a copper content of 99.99% as the material of the conductor (1), selecting a ceramic mica tape as the material of the insulating layer (2), selecting magnesium oxide powder with a purity of 99% as an inorganic flame retardant, preparing a low-smoke halogen-free flame-retardant polyolefin with a melt flow rate of 2g / 10min as the material of the sheath (5), and adding 2%-3% nano-montmorillonite and 5%-8% magnesium hydroxide to the low-smoke halogen-free flame-retardant polyolefin formula; S2. Conductor twisting: preheat the single-filament copper conductor at 95-105℃ for 10-15 minutes, and twist it in layers. The inner and outer twisting directions are opposite. The right pitch of the inner layer is 10-13 times the conductor diameter, and the left pitch of the outer layer is 15-18 times. The tension is within ±3%; S3, insulation wrapping, firstly, the copper conductor is ultrasonically cleaned and passivated, and the ceramic mica tape is wrapped in the twisting direction of the copper conductor, with 3 layers and an overlap rate of 15%; S4, cabling, twisting five insulated wire cores into a cable core in a star-twisted arrangement. During the cabling process, magnesium oxide powder is added as an inorganic flame retardant to fill the gaps between the wire cores. A precise metering spiral feeding device is used to control the filling amount of magnesium oxide powder, and the filling factor is 0.8-0.85; S5, wrapping protection, using cleaning tools to remove dust, oil and other impurities on the surface of the cable core to ensure that the surface of the cable core is clean, and then placing the ceramic silicone tape (5) on a special pay-off stand of the wrapping equipment, adjusting the pay-off tension through a tension closed-loop control system, and controlling the tension fluctuation within ±2%, starting the wrapping machine, so that the cable core starts to rotate at a constant speed or pull forward at a constant speed, and at the same time, the ceramic silicone tape (4) is wrapped around the outside of the cable core according to the set 3-layer wrapping and 15% overlap rate; S6, sheath extrusion, low smoke halogen-free flame retardant polyolefin, nano-montmorillonite, magnesium hydroxide and other materials are fully mixed in a high-speed mixer, stirred at 1300-1800r / min for 25-32 minutes, screw speed 38-40r / min, extrusion temperature 155-185℃, sheath thickness 1.4-1.6mm, first 16-20℃ water cooling for 3-4 minutes, then 24-28℃ air cooling for 7-9 minutes; S7. Performance testing: Conduct line integrity tests in accordance with GB / T19216.21-2003 and GB / T19216.2-2021 standards.
5. The processing technology of a flexible ceramic mineral insulated highly flame retardant and fireproof cable according to claim 4 is characterized in that: During the twisting process, the DC resistance of the conductor (1) does not exceed 0.017241Ω·mm at 20°C. 2 / m.
6. The processing technology of a flexible ceramic mineral insulated highly flame retardant and fireproof cable according to claim 4, characterized in that: Before being added into the low-smoke halogen-free flame-retardant polyolefin, the nano-montmorillonite is first mixed with an appropriate amount of polyethylene wax in a high-speed mixer at a stirring speed of 1000-1500r / min for 20-30 minutes.
7. The processing technology of a flexible ceramic mineral insulated highly flame retardant and fireproof cable according to claim 4, characterized in that: The raw material of the ceramicized silicone belt (4) is first stirred at a low speed of 300-500 r / min for 6-9 minutes at 40-60°C, and then kneaded at a high speed of 1000-1500 r / min for 25-35 minutes.
Citation Information
Patent Citations
Ceramic polyolefin insulated high-flame-retardant fireproof cable and preparation process thereof
CN114171247A
Ceramic silicon rubber and preparation method thereof
CN106046797A
High-safety transponder data transmission cable and manufacturing method thereof
CN107945965A
Processing method of fireproof cable
CN111681832A
Manufacturing method of communication cable special for cruise ship
CN115206601A